(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study investigated the culture and inclusion rate of Chlorella vulgaris in the diet of Clarias gariepinus. Pure sample of C. vulgaris isolate liquid of 50mls were each dissolved in 30% of pure poultry manure, which was later filtered and each poured into 70 liters fish tanks that contained 50 liters of water each and allowed to be illuminated by sunlight for 16 days to enhance C. vulgaris multiplication. The C. vulgaris matrix was harvested, filtered and incorporated in fish feed at 0%, 10%, 20%, 30% and 40% inclusion rates as feed supplement. The experiment was laid in a completely randomized design and treatments were replicated 3 times in 15 fish tanks. Ten juveniles of Clarias gariepinus were stocked per tank and fed for 16 weeks at 5% body weight per day. Proximate analysis of C. vulgaris matrix showed, Ash(30%), Fibre (10.48%), Protein(32.41%) and metabolizable energy(262kcal/g).The water samples analyzed for various physico-chemical parameters like temperature (26.79 ± 27.130 C), pH (5.92 ± 6.34), dissolved oxygen (5.82 ± 6.05mg/l), transparency (15.84 ± 16.70cm) and ammonia (0.13 ± 0.24mg/l) were within the recommended range for Clarias gariepinus culture. Lower values of dissolved oxygen (5.80 ± 0.20 mg/l) and turbidity (5.57 ± 0.45cm) were observed in the control tanks. These optimal physico-chemical parameters showed that the diet did not significantly deteriorate the water quality, as it contained no potential pollutants and was consumed optimally by the fish. This study recommends the use of C. vulgaris matrix supplement at 20-30% in the diet to improve the growth of C. gariepinus owing to their higher nutritional content.